Religio in rure: Cults and Indigenous Continuity in the Northern Area of the Conventus Carthaginiensis (South-West Carpetania) - Rubio Rivera, Rebeca (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The analysis of religiosity in the rural areas of the northern Conventus Carthaginiensis region (south-west Carpetania) in Roman times allows a glimpse of the worship features and cultic heterogeneity given in this context. Thus, despite the lack of epigraphic and archaeological evidence, the approach to the question shows the complex dynamics created by the convergence of Roman cults, different forms of syncretism and indigenous traditions, all forming part of a renewed polytheism, perfectly integrated in the plural Roman religious system.
Keywords: Carpetania; indigenous theonyms; roman gods; roman rural religion